PENGEMBANGAN DAN PEMANFAATAN SISTEM INFORMASI BERBASIS KNOWLEDGE MANAGEMENT UNTUK MEMBENTUK SHARING CULTURE PADA FAKULTAS SAINS DAN TEKNOLOGI UIN SGD BANDUNG - Cecep Nurul Alam; Mohamad Irfan (JURNAL ISTEK, 2011)
Currently existing information systems at the Faculty of Science and Technology UIN SGD Bandung focused on academic information systems only. While the use of academic information outside together in order to support service to consumers and sharing knowledge are still rare. Application service is an information management system and a web-based desktop dedicated to the educational institutions to simplify the complexity of the administrative process and take advantage of efficiencies in education-related activities. Application service is a customized software provided with many modules integrated automaton cycle of student life, academic systems, financial management systems and staff. It is very suitable for various educational institutions including universities.